Born–Oppenheimer and Renner–Teller coupled-channel quantum reaction dynamics of O(3P) + H2+(X2Σg+) collisions. Issue 36 (28th September 2015) - Gamallo, Pablo; Defazio, Paolo; González, Miguel; Paniagua, Miguel; Petrongolo, Carlo
<x xml:space="preserve">Abstract</x> We present Born–Oppenheimer (BO) and Renner–Teller (RT) time dependent quantum dynamics studies of the reactions O(3P) + H2+(X2Σg+) → OH+(X3Σ−) + H(2S) and OH(X2Π) + H+.